GEOLOGY AND 3D STATIC RESERVOIR MODELING OF N FIELD, TALANG AKAR FORMATION, SOUTH PALEMBANG SUBBASIN, SOUTH SUMATRA BASIN - CONG, ERICKO
N Field is a field located in the South Palembang Sub-Basin, South Sumatra Basin. N Field has Talang Akar formation as the main reservoir. The research was carried out by conducting coredescriptions, mudlog analysis, structure interpretation and faults from seismic, and data analysis of wireline logs. Description of core rocks and mudlog analysis used in facies analysis assisted with wireline logs data to conduct electrofacies and stratigraphic sequence correlations. Wireline log data is also used in conducting petrophysical analysis to find reservoir property values, namely water saturation, effective porosity and shale volume. Seismic data is used to find structures and faults that are useful for being the home of the model. In the data modeling phase the data analysis is carried out for all facies and all properties in each facies and each zones. From the model made, the volume can be determined after the cutoff of reservoir properties and depth of hydrocarbon contact are determined. From the analysis conducted in this study, it was determined that there are 4 interest intervals, namely intervals Angsa, Beruang, Cacing and Domba. With two facies associations in the form of Distributary mouthbar deltafront and prodelta mud or mudflat. The main structure is an anticline with east-werst trend with a total STOOIP volume of 7.9 MMSTB.